OLIGARK SEBAGAI RENT SEEKER: HARUSKAH? - Vellayati Hajad (Jurnal Public Policy, 2017)
This article talks about the emergence of oligarchs in West Aceh district. Oligarch is referred to here are  those who dominate  limited  resources. Furthermore,  this paper aims  to examine  the practice of rent seeking  that played by businessmen after  the  local election process. Based on the study it can be concluded that; First, there is a strong connection between businessmen and candidates; clientelistic both emerging businessman who work on  the basis of patronage; and third the practice of rent seeking in the distribution of government projects.  Keyword: oligarch, rent seeker, local election, democracy